Comparison of candida HSP90 protein content and gene expression in Iranian and Malaysian candida-infected patients - Khalili, Vajihozaman (2013)
Introduction: Hsp90 is one of the most abundant and conserved proteins in eukaryotes such as fungal pathogens. Hsp90 is involved in the stability and biosynthesis of proteins required for making the cell wall and is involved in determining cell wall thickness, especially at high temperature. Its interaction with some specific proteins is necessary in order to increase Candida resistance against lytic enzymes and high temperature for continual viability and adaptation to stress conditions. General Objective: To compare the concentration and gene expression of HSP90 in Candida species from Malaysian and Iranian populations in in vitro and in vivo and the role of this protein in the pathogenesis of Candida species. Specific Objectives 1) To determine the amount of HSP90 and its gene expression in different Candida species isolated from Iranian and Malaysian patients. 2) To isolate HSP90 from different Candida species via chromatography techniques. 3) To evaluate HSP90 gene expression in different Candida species via Realtime PCR. 4) To determine differences in the amount and gene expression levels of HSP90 in Candida spp i) isolated from human patients, ii) isolated from mice kidneys and iii) under the shock conditions (25ºC and 42ºC). 5) To investigate possible correlations between the HSP90 levels and gene expression with Candida spp virulence during infection. 6) To establish systemic and non-systemic candidiasis in a mouse model and to evaluate the amounts and gene expression levels of HSP90. Methodology: In this thesis, Hsp90 concentrations and gene expression levels of Candida species in sixteen Malaysian and sixteen Iranian patients were investigated in response to temperature changes. Following purification and measurement of Candida Hsp90, evaluation of HSP90 gene expression levels was performed in vitro and in vivo conditions in Candida species including C.krusie, C. parapsilosis, C. albicans and C. tropicalis. In both systemic and nonsystemic infections the gene expression and amount of HSP90 were evaluated at three situations: i) Candida Hsp90 obtained from Malaysian and Iranian patients , ii) Hsp90 isolated from mouse kidneys infected with Candida cells and iii) Candida Hsp90 after treatment with temperatures 25˚C (low temperature) and 42˚C (thermal shock). Hsp90 purification was performed by two kinds of ion exchange and affinity chromatography using DEAE-Cellulose and hydroxyapatite respectively. Real-time PCR was used in order to evaluate the gene expression of Hsp90. Result: The results showed that Hsp90 concentrations and gene expression levels in isolates obtained from both human patients and kidneys of mouse infected with Candida cells were higher in C. albicans compared to non-albicans Candida in both Malaysian and Iranian populations (p<0.05). A significant increase was observed in the amount and gene expression of Hsp90 isolated from Malaysian patients in comparison with Iranian patients in both systemic and nonsystemic infections (p<0.05). In both populations, the highest gene expression and concentration of Hsp90 was observed in Candida cells after at thermal shock (42˚C) treatment, followed by Candida isolated from mice kidneys. An increase in the amount and gene expression level of Hsp90 was seen in mice body because when Candida cells entered mouse’s body, they encounter different stress factors such as heat and a powerful immune system in this case Hsp90 increased as a defensive response to protect Candida cells in order to survive and maintain viability leading to cell proliferation and more infection in the body. An increase in gene expression was observed in the Malaysian isolates compared to the Iranian samples at different temperatures, but there was a significant difference only in Candida cells isolated from patients (before injection) (p<0.05). Conclusion: Despite the existence of homologies in Hsp90, there are differences at Hsp90 concentration and gene expression in the two populations at different conditions. The amount of Hsp90 and gene expression increase in Candida cells entering the host body (mice) in order to battle with the strong immune system and other stress factors for the survival and viability of Candida cells leading to more infection in the mice.